Duties Of The Village Head In Implementing Village Development (Case Study in Paku Alam Village, Banjar Regency) - Shofia, Finka; Fitriah , Nikmah; Nofrizal , Deni; Mahendra Abdi , Muhammad (LEGAL BRIEF, 2024)
Law Number 6 of 2014 Concerning Villages explicitly assigns tasks to the village government, namely administering government, implementing development, community development, and community empowerment based on Pancasila, the 1945 Constitution of the Republic of Indonesia, and Unity in Diversity. To find out the implementation of the village head's duties in carrying out village development in the village of Paku Alam and to know the arrangements regarding sanctions against village heads who are not optimal in carrying out village development tasks. In research this writer uses empirical research. The Head of Paku Alam Village has carried out his duties and functions as the most important element for the community in carrying out village infrastructure development based on the APBDes. Based on the results of observations it was found that there is still uneven infrastructure development. Meanwhile, legal sanctions if the village head does not carry out his duties in village development are administrative sanctions ranging from reprimand to dismissal as village head. Meanwhile, criminal sanctions are applied if there are criminal acts such as corruption, abuse of authority and other criminal acts. The Village Head has carried out his duties and functions in carrying out village development, but there is still uneven infrastructure development. There are two sanctions for village heads who do not carry out their duties, namely administrative sanctions and criminal sanctions